L’identité professionnelle des gestionnaires des organisations de la santé : un sale boulot requérant un courage managérial ? - Sylvie St-Onge; Line Provost (Perspectives Interdisciplinaires sur le Travail et la Santé)
While managers of health care organizations face severe challenges, their profession is often under-appreciated and criticized. Relying on the concepts of "social identity" and "professional identity" as well as that of "dirty work", our study explores the identity threats faced by health care managers and the strategies they adopt to overcome them. Evidence gathered from interviews shows that health care managers, especially those who are not medical practitioners, perceive that they are considered as heartless and inefficient bureaucrats, both within their institution and outside. They tend to fight the stigma attached to these attributes by using a variety of offensive and defensive strategies. For example, they seek to explain their humanity and how their work adds value. Likewise, they promote and defend the idea that managerial courage is needed to make the difficult decisions required by their jobs.